Convex border of peripheral non-small cell lung cancer on CT images as a potential indicator of pleural invasion. Issue 42 (October 2017) - Hsu, Jui-Sheng; Jaw, Twei-Shiun; Yang, Chih-Jen; Lin, Shiou-Fu; Shih, Ming-Chen Paul; Chou, Shah-Hwa; Chong, Inn-Wen; Lin, Ming-Yen; Chiang, I-Chan
Abstract : Abstract: The aim of the study is to evaluate the use of the tumor border in peripheral non-small cell lung cancer (NSCLC) as an indicator of pleural invasion. This retrospective study was performed at a single tertiary center. The analysis of 136 patients with peripheral NSCLC included 101 (74.3%) patients with pathologically proven pleural invasion and 35 (25.7%) patients without pleural invasion. The tumor borders on conventional computed tomography (CT) were classified into 5 types on lung window setting: type 1, S or reverse S border with a blunt angle; type 2, sharp angle; type 3, concave border with a blunt angle; type 4, straight border with a perpendicular angle; and type 5, convex border with a perpendicular or blunt angle. In patients with more than 1 tumor border type, the priority was type 5, 4, 3, 2, and 1. Blunt angle, pleural contact >3 cm, and adjacent pleural thickening were also recorded for comparison with pleural invasion of peripheral tumors. Tumor border types 2 and 5 significantly differed between patients with and without pleural invasion ( P = .001 and P < .001, respectively). Patients with and without pleural invasion did not significantly differ in tumor border type 1, tumor border type 3, tumor border type 4, blunt angle, pleural contact >3 cm, or pleural thickening. Tumor border type 5 was a moderate indicator of pleural invasion with positive LR, 5.20; accuracy, 57%; sensitivity, 45%; specificity, 91%; PPV, 94%; and NPV, 36%. Tumor border type 2 was a weak indicator of pleural invasion with positive LR, 0.51; accuracy, 34%; sensitivity, 34%; specificity, 34%; PPV, 60%; and NPV, 15%. Tumor border type 5 has a high PPV and high specificity for predicting pleural invasion by peripheral NSCLC.